Effect of Light Color and Auxin on Callus Induction and Development in Amorphophallus muelleri Blume. - Popy Hartatie Hardjo; Michael Anthony Thongiratama; Fenny Irawati; Didik Pudji Restanto (Vegetalika, 2025)
Porang (Amorphophallus muelleri Blume) is a significant player in the international market, but its slow seedling growth rate is a major concern. This study, which holds significant implications for porang cultivation, aimed to accelerate the seedling growth phase through the induction of adventitious shoots from callus proliferation. We explored the use of plant growth regulators (PGRs), specifically auxins (NAA and 2,4-D) and cytokinins (BAP), in combination with variations in light color (white and white-blue). The observed parameters included the time of first callus and adventitious shoot emergence, callus growth, number of adventitious shoots, and callus coloration. Data were subjected to two-way analysis of variance (ANOVA) to evaluate the effects of plant growth regulator (PGR) type and light quality as independent variables. Statistical significance was assessed at a 95% confidence level using SPSS software. The combination of 1.0 ppm NAA and 0.5 ppm BAP in MS medium under white-blue light effectively accelerated callus induction from bulbil explants, with visible callus formation by day 8 and the fastest proliferation over 7 weeks. Under white light, the same PGR combination also promoted the earliest adventitious shoot formation by day 16 and yielded the highest number of shoots, totaling seven by the end of the culture period.